A Sketch Recognition System for Recognizing Free-Hand Course of Action Diagrams - Hammond, Tracy; Logsdon, Drew; Paulson, Brandon; Johnston, Joshua; Peschel, Joshua; Wolin, Aaron; Taele, Paul (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
Military course-of-action (COA) diagrams are used to depict battle scenarios and include thousands of unique symbols, complete with additional textual and designator modifiers. We have created a real-time sketch recognition interface that recognizes 485 freely-drawn military course-of-action sym- bols. When the variations (not allowable by other systems) are factored in, our system is several orders of magnitude larger than the next biggest system. On 5,900 hand-drawn symbols, the system achieves an accuracy of 90% when con- sidering the top 3 interpretations and requiring every aspect of the shape (variations, text, symbol, location, orientation) to be correct.